A literature review of cost–effectiveness analyses of prostate-specific antigen test in prostate cancer screening. (June 2013) - Garg, Vishvas; Gu, Ning Yan; Borrego, Matthew E; Raisch, Dennis W
Prostate cancer is the most common non-skin cancer in American men, and prostate-specific antigen (PSA) testing is its common screening procedure. In May 2012, the US Preventive Services Task Force recommended against PSA-based screening. These recommendations contradict the current recommendations of other organizations such as the American Urological Association. The authors conducted a systematic review of PubMed, EMBASE and Cochrane to examine the published literature reporting the cost–effectiveness of PSA-based screening. The authors found ten studies each for US and non-US jurisdiction population. All reviewed studies concluded PSA-based screening to be cost effective in younger men (≤60 years of age) and at higher PSA levels (≥3 ng/ml). Further cost–effectiveness analyses reflecting latest clinical practice and current perspectives regarding adverse outcomes of potentially unnecessary treatment are required, especially from the US government perspective.